Peningkkatan Hasil Belajar Peserta Didik Dengan Penerapan Model Pembelajaran Carousel Feedback - Laidin Laidin (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
This study aims to determine the application of Carousel Feedback learning models in social studies subjects IV class at SDN Ipi Ende and to determine student learning outcomes in social studies subjects IVA at SDN Ipi Ende with the application of Carousel Feedback models. This research was conducted using research methods class action (CAR) consisting of two cycles. Each cycle consists of four stages namely; observation, planning, action and reflection. Data collection techniques used in this study were tests, observations, interviews, and documentation. The collected data were analyzed descriptively qualitative and quantitative descriptive. The results showed that carousel feedback learning model can improve student learning outcomes. This can be seen from the increase in the percentage of student learning outcomes that have increased, seen from the percentage of classical completeness that is 75% in the first cycle to 100% in the second cycle.